2020
DOI: 10.3390/nano10122493
|View full text |Cite
|
Sign up to set email alerts
|

Can an InChI for Nano Address the Need for a Simplified Representation of Complex Nanomaterials across Experimental and Nanoinformatics Studies?

Abstract: Chemoinformatics has developed efficient ways of representing chemical structures for small molecules as simple text strings, simplified molecular-input line-entry system (SMILES) and the IUPAC International Chemical Identifier (InChI), which are machine-readable. In particular, InChIs have been extended to encode formalized representations of mixtures and reactions, and work is ongoing to represent polymers and other macromolecules in this way. The next frontier is encoding the multi-component structures of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 156 publications
0
40
0
Order By: Relevance
“…The surface of a solid is a complex and dynamic entity, that can actively interact with the surrounding medium, e.g., undergoing protonation/deprotonation, adsorbing/desorbing solvent molecules, ions, and biomolecules, or assisting the precipitation of compounds [ 150 ]. In this view, and taking inspiration from chemo-informatics, the future possibility to encode multi-component structures of nanomaterials in a machine-readable format was foreseen [ 151 ]. Information on size, shape, internal structure, and surface characteristics, possibly including ligands and surface defects on uncoated nanomaterials, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The surface of a solid is a complex and dynamic entity, that can actively interact with the surrounding medium, e.g., undergoing protonation/deprotonation, adsorbing/desorbing solvent molecules, ions, and biomolecules, or assisting the precipitation of compounds [ 150 ]. In this view, and taking inspiration from chemo-informatics, the future possibility to encode multi-component structures of nanomaterials in a machine-readable format was foreseen [ 151 ]. Information on size, shape, internal structure, and surface characteristics, possibly including ligands and surface defects on uncoated nanomaterials, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A longer-term goal of this machine learning project is to keep pace with developments in the InChI community for representing more complicated substances, which step outside of the realm of the well-defined small molecules that make up most fine chemicals. These include polymers, 13 nanomaterials, 14 biomaterials, 15 enumerative sets, 16 reaction products, 17 and many other scenarios where some facts are known about the nature of a component but for various reasons it is not possible to represent it as an atomic connection table. Establishment of a suitable data structure for describing these substances is a subject of active research, for which several domain-specific standards are expected to emerge in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 A study with gold nanoparticles with different surface charges showed that when NPs are coated with serum proteins, the resulting zeta potential was the same for all the particles. 47 Surface charge and porosity are both intrinsic morphological properties describing the nanotopography of NPs, 48 which has previously been shown to greatly influence the cell interactions of nanomaterials. 30 The surface area and pore size were determined via nitrogen sorption using Brunauer-Emmett-Teller analysis, which revealed an area of 1259.8 m 2 g −1 and average pore size of 3.9 nm for MSNPs, while high-resolution TEM revealed a pore size of 4.1 ± 0.3 nm (Fig.…”
Section: Np Properties Impact the Formation Of Protein Coronawhat Determines Selectivity In Protein Binding?mentioning
confidence: 99%